No social media for six hours? The emotional experience of Meta's global outage according to FoMO, JoMO and internet intensity. (January 2023) - Eitan, Tal; Gazit, Tali
Abstract: On October 4, 2021, a severe technical service failure of Meta (previously Facebook) caused a worldwide "outage" for 6 h. Billions of people, not able to access their social media accounts, experienced different levels of stress. This study took advantage of these unique circumstances to test the stress caused by sudden lack of online access using three main factors: the fear of missing out (FoMO) effect, social media intensity, and demographic factors. In the two days immediately following this event, we conducted an online survey, with 571 adults responding. Using both quantitative and qualitative analyses, data were collected to explore the emotional experiences and predictors of the stress adults underwent during the social media outage. The content analysis revealed four types of reactions: (1) feeling anxious at first, but then feeling better after realizing the outage was global; (2) having only negative feelings; (3) having only positive feelings and even experiencing a version of the joy of missing out (JoMO); and (4) feeling indifferent. A hierarchical regression indicated that stress can be significantly predicted by FoMO, social media intensity, emotional experience, age, and marital status. In addition, FoMO and intensity were found to be mediators between age and stress. Finally, we found associations between stress and gender and employment, with self-employed women experiencing less stress than men and not self-employed women experiencing more stress than men. The findings are discussed in light of the FoMO vs. JoMO effects, the social comparison theory, and the role of demographic factors in reducing or increasing stress when social media is not available. Highlights: This study tested stress caused by the social networks' October 4, 2021 outage. We used both quantitative and qualitative methods to explore the emotional experience. Content analysis revealed 4 types of reactions, including joy of missing out (JoMO). FoMO, Internet intensity, age, and marital status were found as predictors of stress. A significant interaction was found between gender and employment regarding stress.